Implementasi Nilai-Nilai Kristiani dalam Pembentukan Karakter Siswa Sekolah Dasar Inpres Ngurwalek - Siyena Wee; Teresia Noiman Derung (ARDHI : Jurnal Pengabdian Dalam Negri, 2024)
This research aims to describe the implementation of Christian values ​​in the formation of student character at the Inpres Ngurwalek Elementary School. This research uses qualitative methods by collecting data through observation and in-depth interviews. This research aims to reveal the strategies implemented by schools in integrating Christian values ​​into the curriculum and extracurricular activities. The research results show that the school has made various efforts to instill Christian values ​​in students, such as through thematic learning, religious activities, and character development. However, there are still several challenges that need to be overcome to optimize the implementation process.